Chemical Properties and Mineralogical Composition of Soils in Original site at Coal Mining Area - Ria Rachel Paranoan (AGRITROPICA : Journal of Agricultural Sciences, 2019)
Soil minerals and  chemical properties play an essential role  in agricultural, especially to know  the  availability of soil nutrient reserve. The objective of the study was to investigate soil chemical properties and mineralogical  composition. of sand fraction in original area. The study was conducted in two stages. The  First stage was in the field and the second stage was in the laboratory. The field study was at Original area PT. Khotai Makmur Insan Abadi, Kutai Kartanegara, East Kalimantan. Soils were sampled from each horizon of the profile. The second stage was in the Laboratory. The chemical analysis was conducted    in  the Soil Laboratory,  Agriculture Faculty,  Mulawarman University.  The Mineralogical composition of fine sand fractions was  conducted in Pusat penelitian tanah Bogor, with line counting method using Microscope Polaritation (MP). The results of chemical characteristics indicated that  low to very low content of organic matter, soil reactions are acid throughout the horizon,  very low to moderate  base satration, low to moderate soil cation exchange capacity, high of Al saturation.  Sand fraction composition was dominated by resistant minerals (quartz and opaque). On the other hand the easily weatherable minerals are not detected in the original area. One of the reason soil has low  CEC is, because the composition of sand fraction in the soil dominated by quartz.